Thinking from the Body: New Theater in El Salvador in the 1970s - Roque Baldovinos, Ricardo (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
Starting with a survey of the theatrical movement in El Salvador during the revolutionary turmoil of the 70s, this article discusses different Avant-Garde theatrical aesthetics concerned in developing a practice of thinking from the body. Engaging in a discussion with the main concepts of Brecht epic theatre and its Latin American followers (Enrique Buenaventura, Santiago García y Augusto Boal) and the aesthetic debate about their implications (Benjamin, Jameson, Rancière), this article demonstrates that New Theatre evidences the social production of the body as mechanism of subjectivation and the emancipatory possibilities of new forms of bodily experience offered by the new dramatical vocabularies.
Keywords: aesthetics; theatre; Avant-Garde; autoritarianism; revolution; Latin America; El Salvador